1983
DOI: 10.1007/bf00711947
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the antigenic sites of actin: a comparative study of the immunogenic crossreactivity of invertebrate actins

Abstract: The structural homologies of invertebrate actins with cytoplasmic vertebrate actins have recently been substantiated by comparative sequence analyses. This suggests that cytoplasmic actin is the ancestral precursor of smooth and striated muscle actin in vertebrates. We have raised antibodies in rabbits against a number of invertebrate muscle actins and have characterized the antisera by means of the highly sensitive ELISA method, which allows quantitation of nanomolar amounts of actin. Despite the fact that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

1984
1984
1990
1990

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 60 publications
2
11
0
Order By: Relevance
“…15) . Preabsorption of antiserum with insect myofibrils was not sufficient to completely abolish labeling, probably due to the marked species-specific properties of the antibody (21). Nonimmune sera were occasionally found to label the basement membrane weakly even after extensive blocking procedures, probably owing to the presence of autoimmune antibodies to actin which are frequently present in human and in rabbit sera.…”
Section: Subcellular Localization Of Actinmentioning
confidence: 99%
“…15) . Preabsorption of antiserum with insect myofibrils was not sufficient to completely abolish labeling, probably due to the marked species-specific properties of the antibody (21). Nonimmune sera were occasionally found to label the basement membrane weakly even after extensive blocking procedures, probably owing to the presence of autoimmune antibodies to actin which are frequently present in human and in rabbit sera.…”
Section: Subcellular Localization Of Actinmentioning
confidence: 99%
“…There have been previous attempts to induce antibodies to invertebrate actins (De Couet, 1983;Kleeve et al, 1979) but the sera were used without antibody fractionation and presented more or less broad specifity, impeding discrimination between direct effects due to amino-acid substitutions and those linked to related conformational changes. The use of chemical derivatives of actin and proteolytic fragments as immunogens to diversify serum specificity, and the purification of induced antibody populations on insolubilized derivatives thereby localizing the corresponding antigenic epitopes, made it possible to detect substituted sites in actins among the invertebrate phyla.…”
Section: Originmentioning
confidence: 99%
“…In invertebrates, the situation is not well documented (Vandekerckhove & Weber, 1984). Only few complete sequences have been determined (Fryberg et al, 1981;Vandekerckhove & Weber, 1984) and comparisons between actin isoforms are generally based on the variable acidic sequence 1-7 which allows electrophoretic separation by electrofocusing (De Couet, 1983;Huang et al, 1984;Margulis et al, 1982). This short sequence has been determined in numerous vertebrates, but only in some phyla in invertebrates (Vandekerckhove & Weber, 1984).…”
Section: Introductionmentioning
confidence: 97%
“…The proposed involvement (De Couet, 1983;Hambly et al, 1986) of this variable extremity (1-12 sequence) of actins in the reported functional variation has not been confirmed Strzelecka-Golaszewska et al, 1985). This raises questions as to the location and the nature of the amino acid substitutions along the primary structure and the related consequences for the biological role of the isoactin expressed in a particular tissue.…”
Section: Introductionmentioning
confidence: 96%
“…Skeletal-muscle and cardiac striated-muscle actins are of the a-type, smooth-muscle actins of the a-and y-types and cytoplasmic actins of the fi-and y-types (Bulinski et al, 1983). Invertebrate actins, which have been less well analysed (De Couet, 1983), share homologous sequences with cytoplasmic actins (Vandekerckhove et al, 1983). For instance, scallop adductor-muscle actin has been characterized as a fl-like actin (Khaitlina, 1986), in contrast with its location in a striated muscle (Millman & Bennett, 1976).…”
Section: Introductionmentioning
confidence: 99%